Efficient organic terahertz generator with extremely broad terahertz molecular vibrational mode-free range - Shin, Bong Rim; Yu, In Cheol; Shin, Myeong Hoon; Jazbinsek, Mojca; Rotermund, Fabian; Kwon, O. Pil (APL Materials, 2023)
For nonlinear optical materials to be applicable as efficient broadband terahertz (THz) wave generators, low absorption with wide transparency in the THz frequency range is highly important. In this study, we report efficient organic THz wave generators, 2-(4-hydroxystyryl)-1-methylquinolinium 4-bromobenzenesulfonate (OHQ-BBS) single crystals. Interestingly, the OHQ-BBS crystals exhibit a wide molecular vibrational mode-free range in the THz frequency region from 1.7 to 5.1 THz with an absorption coefficient of <20 mm-1. By optical rectification employing 130 fs pump pulses at 1300 nm wavelength, the OHQ-BBS crystals generate extremely broad, dimple-free THz waves in the range of 1.2-5.5 THz. Additionally, a THz electric field that is 20 times higher than the field generated from the widely used ZnTe inorganic crystal is achieved. Therefore, the OHQ-BBS single crystals are highly promising materials for diverse THz photonic applications.
Keywords: Absorption coefficients; Broadband terahertz; Frequency regions; Nonlinear optical materials; Organics; Tera Hertz; Terahertz frequencies; Terahertz frequency range; Vibrational modes; Wave generators